Life adversities of clients seeking advice for suicidal ideation from an online peer counseling service: Characteristics and associations with outcomes - Hildebrand, Anja; Weiss, Maren; Stemmler, Mark (Mediterranean Journal of Clinical Psychology, 2023)
Objective: [U25] Germany is a low-threshold, anonymous and free-of-charge online suicide prevention service for people up to 25 years of age. Its special feature is that counseling is provided by trained and continuously supervised voluntary peers. This study addresses the following research questions: (1) Which life adversities are reported by the clients of [U25]? (2) Are the life adversities intercorrelated? (3) According to patients, do life adversities change during the counseling process? (4) What are the associations between life adversities and outcome measures (e.g., reduction in suicidality or improvement in general situation)? Method: Data was collected through an online survey (n = 318). To measure psychological burden, the presence of 16 life adversities (e.g., problems in relationships) was assessed retrospectively. As the dependent variable, the change in suicidality was measured by means of three newly created items. In addition, a short form of the Bochum Change Questionnaire 2000 (BCQ 2000) was used to assess the patients’ subjectively perceived change due to counseling. Results: Regarding life adversities, the clients were heavily burdened. Throughout the course of counseling, many clients’ situations improved, at least concerning several adversities. Some life adversities significantly correlate with each other, but the correlation is mostly small to moderate. Suicidality is positively correlated with self-harming behaviors and loss of someone close to the advice seekers. Conclusions: Possible starting points for improving online counseling for suicidal adolescents and young adults are discussed.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Adolescence; Life adversities; Online counseling; Peer counseling; Suicide prevention